Household debt and social interactions - Dimitris Georgarakos; Michalis Haliassos; Giacomo Pasini (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
Can concern with relative standing, which has been shown to influence consumption and labor supply, also increase borrowing and the likelihood of financial distress? We find that perceived peer income contributes to debt and the likelihood of financial distress among those who consider themselves poorer than their peers. We use unique responses describing perceived peer characteristics from a Dutch population-wide survey to handle major challenges of uncovering social interaction effects on borrowing: (i) debts, unlike conspicuous consumption, are often hidden from peers, and (ii) location is missing in anonymized data. We employ several approaches to uncover exogenous, rather than correlated, effects.
Keywords: G11; E21; 330; Household finance; household debt; social interactions; mortgages; consumercredit; informal loans